Common Symbols In Eurasia-pacific Unconscious Cultural Heritage: A Case Study Of The Taiwanese 18 Deities' Cult - Sitnikov, Igor (Penerbit Universiti Sains Malaysia (USM Press), 2011)
The case study of the "Temple of 18 Deities" demonstrates a row of stable Eurasian-Pacific religious symbols which were preserved in the Taiwanese religious cult. In the article, the author claims that the traces of those long-lived elements could be found in many other religions and cultures all over EurasiaPacific area, from Ireland to China, Taiwan and Oceania. In the paper, the "Temple of 18 Deities" origin mythology is analysed, the author's fieldwork described, a set of stable symbols in the cult of 18 deities' revealed, and researches devoted to Taiwanese and Chinese popular religion genesis overviewed. In the end, the traces of those symbols in mythologies of other cultures in Eurasia-Pacific cultural area are illustrated, main symbols common meanings analysed, and their origins and stages of transformation reconstructed. In the article on example of the 18 deities' cult in northern Taiwan, the author observes how ideas, beliefs, and values were created and transmitted in religious cultures during the periods of cultural changes. The author suggests that invisible Eurasian-Pacific common cultural heritage is hidden under umbrellas of different variants of popular religions and superstitions in different cultural traditions all over Eurasia-Pacific, and the case of the Taiwanese 18 deities' cult is an example of such heritage inside Chinese popular religion and folk Buddhism.